Cohort profile: the Martinique Cancer Registry and the quality of life prostate cancer cohort (QoL Prostate-MQ): challenges and prospects for reducing disparities in the Caribbean. Issue 7 (25th July 2018) - Joachim, Clarisse; Veronique-Baudin, Jacqueline; Almont, Thierry; Ulric-Gervaise, Stephen; Macni, Jonathan; Pierre-Louis, Olivier; Godaert, Lidvine; Drame, Moustapha; Novella, Jean-Luc; Farid, Karim; Vinh-Hung, Vincent; Escarmant, Patrick
Abstract : Purpose: Recording cancer data in cancer registries is essential for producing reliable population-based data for service planning, monitoring and evaluation. Prostate cancer (PCa) remains the most frequent type of cancer in terms of incidence and mortality in men in the Caribbean. The quality of life PCa cohort will assess quality of life and patient outcomes in Martinique using a digital platform for patient-reported outcome measures. Participants: The Martinique Cancer Registry database is the largest clinical database among the French population-based cancer registries in the Caribbean, including more than 38 000 cancer cases, with 1650 new cancer cases per year, including 550 new PCa cases per year (2010–2014 latest period). In 2018, follow-up will include vital status, assessment of quality of life with the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (QLQ) Core 30 and the Prostate cancer module QLQ-PR25. Urinary incontinence and erectile dysfunction recorded prior to treatment will be analysed 1 and 5 years after treatment. Findings to date: The registry includes data on circumstances of diagnosis, clinical stage at diagnosis. For PCa, the registry includes blood prostate-specific antigen level at the time of diagnosis, Gleason score and primary treatment. Future plans: Further studies will provide detailed data regarding the quality of diagnosis and management of patients with PCa in Martinique; analysing quality of care will be the next challenge. Quality of life and patient outcomes will be evaluated using a digital platform for patient-reported outcome measurement and electronic records.